Does in vitro application of pentoxifylline have beneficial effects in assisted male reproduction?. (28th October 2020) - Mahaldashtian, Maryam; Khalili, Mohammad Ali; Nottola, Stefania Annarita; Woodward, Bryan; Macchiarelli, Guido; Miglietta, Selenia
Abstract: Application of nonspecific phosphodiesterases inhibitors, such as pentoxifylline (PTX), is a strategy utilised to aid sperm selection from immotile sperm samples prior to ICSI. No extensive studies have yet been performed to verify the safety of the clinical outcomes of ICSI after PTX administration. In this article, we summarise the data reported in the literature that assess the implication of in vitro usage of PTX on sperm parameters, as well as clinical outcomes during assisted male reproduction programme.